The Changing Faces of Ireland - Darmody, Merike; Tyrrell, Naomi; Song, Steve; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2011)
Before the economic boom of the 1990s, Ireland was known as a nation of emigrants. The past fifteen years, however, have seen the transformation of Ireland from a country of net emigration to one of net immigration, on a scale and at a pace unprecedented in comparative context. As a result, Irish society has become more diverse in terms of nationality, language, ethnicity and religious affiliation; and these changes are now clearly reflected in the composition of both primary and secondary schools, presenting these with challenges as well as opportunities. Despite the increased number of ethnically-diverse immigrant children and young people in the Ireland, currently there is a paucity of information about aspects of their lives in Ireland. This book is aimed at contributing to this gap in knowledge. This edited collection will be of interest to researchers in the fields of migration studies, childhood studies, education studies, human geography, sociology, applied social studies, social work, health studies and psychology. It will also be a useful resource to educators, social workers, youth workers and community members working with (or preparing to work with) children with immigrant and ethnic minority backgrounds in Ireland.
Keywords: Educational sociology; Sociology of Education